Simulation of the process of non-isothermal crystallization process of thermoplastic slurry BeO in the annular cavity of the casting plant - Саттинова, З (BULLETIN OF THE L.N. GUMILYOV EURASIAN NATIONAL UNIVERSITY. PHYSICS. ASTRONOMY SERIES, 2022)
The results of calculations of the mathematical model of motion, heat transfer and the process of hardening of the slurry mass in the annular cavity are given. The slurry mass is highly concentrated structured system where the mineral phase is beryllium powder and liquid phase is an organic binder (paraffin, oleic acid and beeswax). The fields of velocity, temperature, density of the slurry, changes heat flux density on the wall of the cavity are obtained. The structure of the crystallization front and thixotropic flow is determined on the basis of a rheological model of viscoelastic fluids and the heat transfer from the slurry to the surface of the wall is determined with criterion Bio (Bi). The results as the form of graphs shows that the crystallization rate depends on the different parameter regimes and construction data of the molding cavity of the installation for casting ceramic products.